Matters of the Heart: The Compelling Link between Ischemic Heart Disease and Psychiatric Disorders - Vinall, Phil (MD Conference Express, 2009)
Over the last 15 to 20 years, investigators have slowly started to unravel a fascinating link between psychiatric disorders and cardiovascular disease.